Level of Mother's Knowledge About Nutrition for Pregnant Women in Rimba Soping Village Padangsidimpuan Angkola Julu District Year 2022 - Siregar, Rya Anastasya; Novita Sari Batubara; Nur Aliyah Rangkuti (International Journal of Public Health Excellence (IJPHE), 2022)
Nutrition Mother pregnant is food healthy and balanced a must consumed Mother during her pregnancy, with two servings of people who don't pregnant. nutritional status Mother before and during pregnant can influence growth fetus. If the nutritional status was normal before and during pregnant possibility big will give birth to healthy baby, enough month with normal weight. In other words quality newborn baby is very dependent on circumstances nutrition Mother before and during pregnant. A Mother pregnant will give birth to healthy baby when level health and nutrition are in good condition. However until moment This Still Lots Mother experiencing pregnant problem nutrition specifically nutrition not enough like not enough Energy Chronic (CED) and nutritional anemia. As for goals study This is for know knowledge Mother about nutrition Mother pregnant in Rimba Soping village Subdistrict Padangsidimpuan Angkol Julu. The research design used in study This is descriptive, with big sample of 50 people. Method taking sample is with accidental sampling technique namely take chance sample There is or ready. Study This done on the month January-March 2022. Instruments study This use excess questionnaire before being tested for validity content as many as 20 questions knowledge. Research results show that knowledgeable Good as many as 29 people (58%), and knowledgeable Enough as many as 12 people (24%), and knowledgeable not enough as many as 9 people (18%). Expected power health that has competence in give care and counselling during pregnancy, midwife must capable give quality prenatal care tall For optimizing health during pregnancy including counseling health about importance nutrition Mother pregnant.